THE EFFECT OF PHYSICAL WORK ENVIRONMENT AND COMPENSATION ON JOB SATISFACTION OF MIE GACOAN RATULANGI EMPLOYEES - Saskiya Febriani; Agung Widhi Kurniawan; Rahmat Riwayat Abadi (Jurnal Manajemen, 2026)
Abstract: This study aims to examine and analyze the influence of the physical work environment and compensation, both partially and simultaneously, on employee job satisfaction at Mie Gacoan Ratulangi. This study is expected to provide an overview of the factors that influence employee job satisfaction levels, supporting improved performance and workplace comfort. This study used a quantitative approach. Data were collected through questionnaires distributed to all 65 employees of Mie Gacoan Ratulangi. The data analysis technique used was multiple linear regression analysis with the help of SPSS (Statistical Package for the Social Sciences) to test the effect of the independent variables (Physical Work Environment and Compensation) on the dependent variable (Job Satisfaction). The results of the study indicate that the physical work environment has a positive and significant effect on employee job satisfaction. Compensation also has a positive and significant effect on employee job satisfaction. Simultaneously, the physical work environment and compensation significantly influence employee job satisfaction. This indicates that a comfortable work environment and fair compensation can increase employee job satisfaction..Keywords: Physical Work Environment, Compensation, Employee Job Satisfaction.